2020
DOI: 10.1001/jamanetworkopen.2020.24596
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Balanced Crystalloids vs Saline in Adults With Diabetic Ketoacidosis

Abstract: IMPORTANCE Saline (0.9% sodium chloride), the fluid most commonly used to treat diabetic ketoacidosis (DKA), can cause hyperchloremic metabolic acidosis. Balanced crystalloids, an alternative class of fluids for volume expansion, do not cause acidosis and, therefore, may lead to faster resolution of DKA than saline. OBJECTIVE To compare the clinical effects of balanced crystalloids with the clinical effects of saline for the acute treatment of adults with DKA. DESIGN, SETTING, AND PARTICIPANTS This study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 32 publications
2
73
1
2
Order By: Relevance
“…One study ( 28 ) reported the subgroup of DKA patients from two linked cluster RCTs ( 14 , 15 ) and was treated as a single RCT for the purposes of our analysis. These linked cluster RCTs enrolled a total of 172 patients with DKA; however, after applying the design effect and sample size reduction, we used a functional sample size of 106 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study ( 28 ) reported the subgroup of DKA patients from two linked cluster RCTs ( 14 , 15 ) and was treated as a single RCT for the purposes of our analysis. These linked cluster RCTs enrolled a total of 172 patients with DKA; however, after applying the design effect and sample size reduction, we used a functional sample size of 106 patients.…”
Section: Resultsmentioning
confidence: 99%
“…One trial ( 27 ) used both Ringer’s lactate and PlasmaLyte due to a shortage in Ringer’s lactate that occurred during the study period. Another trial ( 28 ) allowed for the use of either Ringer’s lactate or PlasmaLyte at the discretion of the treating clinical team. Supplemental Table 4 ( http://links.lww.com/CCX/A890 ) presents risk of bias of the included RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported the duration of insulin infusion in adults (Self et al [8]) for DKA. The study reported normal saline requiring more time, 13.4 h (11-17.9), than 9.8 hours (5.1-17) in balanced solutions before switching to subcutaneous insulin.…”
Section: Duration Of Insulin Infusionmentioning
confidence: 99%
“…These study results suggest that balanced crystalloids may be preferable to saline for acute management of adults with DKA. 7 A Cochrane review in 2016 analyzed five small RCTs (total n = 201) comparing subcutaneous injections of insulin analogues (lispro or aspart) to regular insulin IV infusions in patients with mild to moderate DKA. The study revealed that there was no statistical difference in time to resolution of DKA (approximately 11 hours) or rates of hypoglycemia.…”
Section: Review Dka Managementmentioning
confidence: 99%